Vitamin D insufficiency among children with cancer in India - Mohan, Ram; Mohan, Gem; Scott, Julius; Rajendran, Aruna; Paramasivam, Venkatraman; Ravindran, Manipriya (Indian Journal of Medical and Paediatric Oncology, 2016)
Background: Vitamin D plays an important role in regulating various homeostatic mechanisms and has yet untapped potential in cancer prevention and prognosis. Only a few studies have been done worldwide in relating the Vitamin D levels in pediatric cancer patients to the general population but none so far in an Indian setting to the best of our knowledge. Objective: To compare the Vitamin D levels in a group of children with cancer to that of the general pediatric population and to note differences in the prevalence of Vitamin D insufficiency and make inferences arising from demographic and therapeutic variations. Materials and Methods: Vitamin D levels were found by immuno-chemilumino-metric assay in 102 children (51 cases and 51 controls) over a 6 months period. Results: In comparing the Vitamin D levels of children with cancer and controls from a healthy population we found an increased incidence of Vitamin D insufficiency in cancer children (80.39%) when compared to controls (50.98%) and a much lower mean Vitamin D value in cancer children (22.8 ng/ml) when compared to controls (33 ng/dl). It was also found that cancer children above 6 years had a greater chance for developing Vitamin D insufficiency (P = 0.038) as did children suffering from hematological malignancies (P = 0.025). Conclusion: Our study showed an increased prevalence of Vitamin D insufficiency in children with cancer and hence we suggest routine measurement of Vitamin D levels in children with cancer and subsequent supplementation.
Keywords: Childhood cancer; India; Vitamin D